Effects of various lethal doses of amitriptyline to the length of Calliphoridae larvae - Emira Alifia; Arfi Syamsun; Eustachius Hagni Wardoyo (Faculty of Medicine, Universitas Islam Indonesia, 2020)
Background: Uses of insects to predict Post-mortem Interval (PMI) is important for non-natural causes of death such as drug abuses. Doses of drugs in a corpse are presumed to affect rates of growth and development of insects and relationships to predict the PMI. Objective: This study aims to study effects of various doses of lethal amitriptyline to the length of Calliphoridae larvae stage as the first organism seen on a corpse as well as to assess other factors involved in insect growth such temperatures and humidity.Methods: This study was an experimental research using 24 dead rats as larva’s growth media. These rats were divided into four group: the control group, the first treatment (T1) group, the second treatment (T2) group, and the third treatment (T3) group. The control group was deceased by cervical dislocation representing natural cause of death, while the treatment groups were given various doses of amitriptyline orally. The doses given to T1, T2, and T3 groups were 75 mg, 100 mg and 125 mg, respectively. Next, the rat corpses were put into cages containing Calliphoridae larvae; daily observation was conducted every morning and afternoon until the larvae transformed into pupae. All obtained data were analysed by using a multivariate linear regression analysis, Spearman correlation and Kruskal-Wallis.Results: This study showed that the more doses of amitriptyline, the longer larva cycle and the shorter length of larvae (p<0,05). The life cycle time in the control, T1, T2, and T3 groups were four, five, eight and nine days, respectively. Based on the first day of larva appearance in each group, the control group produced an average length of larvae longer than the T1, T2, and T3 groups, respectively 8.33 mm, 7.33 mm, 4.5 mm and 5.67 mm. However, differences of temperatures and humidity observed in the routine morning and afternoon did not have any differences.Conclusion: Increasing more doses of amitriptyline extended the larva cycle that could cause the larva length to be shorter in the treatment group compared to the control group on the same day. Environmental factors in this study had smaller effects on the larva length growth of the Calliphoridae larvae.